Gender Differences in Popularity and Engagement in Sport Activities among Students - Matej Majerič (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2016)
The main purpose of this research was to analyse the gender differences among students at the University of Ljubljana concerning the popularity of sports and participation in different types and modes of sport activities. The research was done in the 2013 academic year on a random sample of 3% of the students (N=1390). A questionnaire about students' lifestyles was used (Majerič, 2013). In this study, two variables were analysed: the popularity of different sport activities, and different types and modes of sport activities. The data of the variables were analysed with SPSS for Windows. The basic statistical parameters for both variables were calculated. To calculate the gender differences, a t-test for independent samples and a Mann-Whitney U test were run. An analysis of the popularity of different sport activities showed that gender differences were statistically significant in jogging (p=0.000), walking (p=0.000), football (p=0.000), basketball (p=0.000), fitness (p=0.001), aerobics (p=0.002), and dance activities (p=0.009). Analysis of the types and modes of sport activities among students showed that 63.90% of male students and 68.10% of female students were engaged in unorganized types of sport. Gender differences were found to be statistically significant in two types of sport activities: engaged organized in clubs-competitive out of faculty (p=0.000) and engaged in sport organized at the faculty-competitive (p=0.000). Our findings and conclusions provide useful guidance for the closer and wider professional public.